Exploring the Mechanisms of the Spatiotemporal Invasion of Tuta absoluta in Asia - Ritter A. Guimapi; Ramasamy Srinivasan; Henri E. Tonnang; Paola Sotelo-Cardona; Samira A. Mohamed (Agriculture, 2020)
International crop exchange always brings the risk of introducing pests to countries where they are not yet present. The invasive pest Tuta absoluta (Meyrick 1917), after taking just a decade (2008–2017) to invade the entire Africa continent, is now continuing its expansion in Asia. From its first detection in Turkey (2009), the pest has extended its range of invasion at a very high speed of progression to the southeast part of Asia. This study adopted the cellular automata modelling method used to successfully predict the spatiotemporal invasion of T. absoluta in Africa to find out if the invasive pest is propagating with a similar pattern of spread in Asia. Using land cover vegetation, temperature, relative humidity and the natural flight ability of Tuta absoluta, we simulated the spread pattern considering Turkey as the initial point in Asia. The model revealed that it would take about 20 years for the pest to reach the southeast part of Asia, unlike real life where it took just about 10 years (2009–2018). This can be explained by international crop trade, especially in tomatoes, and movement of people, suggesting that recommendations and advice from the previous invasion in Europe and Africa were not implemented or not seriously taken into account. Moreover, some countries like Taiwan and the Philippines with suitable environmental condition for the establishment of T. absoluta are not at risk of natural invasion by flight, but quarantine measure must be put in place to avoid invasion by crop transportation or people movement. The results can assist policy makers to better understand the different mechanisms of invasion of T. absoluta in Asia, and therefore adjust or adapt control measures that fit well with the dynamic of the invasive pest observed.